An Advanced Study on Optimization and Characterization of Nano Aluminum Trihydrate-Based Flame-Retardant Materials in the Rotating Packed Bed Reactor - Pao Chi Chen; L. C. Yang (New Ideas Concerning Science and Technology Vol. 8, 2021)
A CO2/NaAlO2/H2O absorption-reaction system was adopted to prepare nano aluminum trihydate (ATH) particles for cables use in a rotating packed-bed (RPB) reactor (Phase I). The Taguchi experimental design was used to give an orthogonal array, L9(34). The parameters were the speed of rotation (A), gas-liquid flow rate ratio (B), aging temperature (C) and aging time (D), each having three levels. According to the signal/noise (S/N) ratio analysis, the larger-the-better for the BET area (Sw) was found to be A3B3C1D1, while the parameter significance was DABC. Empirical formula for Sw was also obtained and discussed. Subsequently, the optimum size (10.7 nm) of ATH powders were used to blend with the matrix including plastics and additives (Phase II) for characterization further. The examination of composite materials showed that the limiting oxygen index (LOI) was higher than 28, indicating an excellent fire-retarding property. The Taguchi method was used to look for optimum conditions for preparing nano-ATH. The particle size, grain size, powder morphology and thermal analysis were analyzed. The results also showed that the LOI for nano ATH is higher than that bought from the market, while the fire-retarding grade examination (UL-94 test) for both ATHs was found to be of a V-0 grade. In addition, the mechanical properties for nano ATH were measured prior to using the ATH from the market. Finally, the process creates an opportunity to capture CO2 for some industries.